The Effect of Service Quality, Trust, and Product Attributes on Customer Loyalty with Satisfaction as Intervening Variables (Case Study of Batara IB Savings in PT Bank Tabungan Negara (Persero) Tbk. Office Depok Branch) Sharia - Kumba Digdowiseiso; Mayorette Shabrina Ananda (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the influence of Service Quality, Trust, and Product Attributes on Customer Loyalty with Satisfaction as an intervening variable. The research sample consists of 150 Bank BTN savers. A questionnaire was used to collect data, and STATA 16.0 was utilized for analysis. The findings of this study indicate that service quality has a positive and statistically significant effect on customer loyalty, trust has a positive and statistically significant effect on customer loyalty, product attributes have a positive and statistically significant effect on customer loyalty, satisfaction has a positive and statistically significant effect on customer loyalty, and service quality has a positive and statistically significant effect on loyalty. Meanwhile, trust has a positive and significant impact on customer loyalty mediated by satisfaction, and product attributes have a positive and significant impact on customer loyalty mediated by satisfaction.